2017
DOI: 10.1021/acsami.7b04079
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Charges in Polyvinyl Alcohol Networks to Marine Antifouling

Abstract: Semi-interpenetrated polyvinyl alcohol polymer networks (SIPNs) were prepared by integrating various charged components into polyvinyl alcohol polymer. Contact angle measurement, attenuated total reflection Fourier transform infrared spectroscopy, field emission scanning electron microscopy, and tensile tests were used to characterize the physicochemical properties of the prepared SIPNs. To investigate the contribution of charges to marine antifouling, the adhesion behaviors of green algae Dunaliella tertiolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 51 publications
(77 reference statements)
1
34
0
Order By: Relevance
“…In addition to the abovementioned single-component materials, multi-component materials have been designed and synthesized as highly efficient antifouling materials. [22,23] For example, Zhou et al systematically investigated the synergistic effects of combining hydroxyl-abundant polyvinyl alcohol (PVA) with anionic, neutral, or zwitterionic polymers on their antifouling performance. [22] They found that the incorporation of anionic, neutral, or zwitterionic components into PVA enhances the material's antifouling performance against marine algae.…”
Section: Doi: 101002/mabi201800137mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the abovementioned single-component materials, multi-component materials have been designed and synthesized as highly efficient antifouling materials. [22,23] For example, Zhou et al systematically investigated the synergistic effects of combining hydroxyl-abundant polyvinyl alcohol (PVA) with anionic, neutral, or zwitterionic polymers on their antifouling performance. [22] They found that the incorporation of anionic, neutral, or zwitterionic components into PVA enhances the material's antifouling performance against marine algae.…”
Section: Doi: 101002/mabi201800137mentioning
confidence: 99%
“…[22,23] For example, Zhou et al systematically investigated the synergistic effects of combining hydroxyl-abundant polyvinyl alcohol (PVA) with anionic, neutral, or zwitterionic polymers on their antifouling performance. [22] They found that the incorporation of anionic, neutral, or zwitterionic components into PVA enhances the material's antifouling performance against marine algae. Xu et al also synthesized multi-component antifouling materials, zwitterionfunctionalized PEG, and succeeded in preparing antifouling surfaces to which proteins, bacteria, and microalgae can hardly attach.…”
Section: Doi: 101002/mabi201800137mentioning
confidence: 99%
See 2 more Smart Citations
“…One major category of antifouling coatings prevents biofoulants from approaching the surface, while the other type weakens the adhesion bonding attached to a surface and allows easy removal with low shear stress for biofoulants, widely known as foulingrelease coatings. More specifically, detailed practices range from surface grafting of hydrophilic polymer brushes (e.g., nonionic, zwitterionic polymers) [1,2] to hydrophilic polymeric networks, [3] polymer coatings incorporating antifoulants, [4,5] hydrophobic fluorogel elastomers, [6] polysiloxane based coatings, [5] self-replenishing coatings, [7] and other nanocomposites with nano/microscale topographies. [8,9] Currently, engineering of surfaces from microphase segregated amphiphilic polymer systems, which combine both hydrophobic and hydrophilic components in one entity, has been constantly gaining attention and recognized as one promising functionalization strategy in various applications including, biocompatible medical implants, devices for biorecognition processes, texturing substrates for supermolecular assemblies, [10,11] and membrane separation processes.…”
mentioning
confidence: 99%